Knowledge-Based Innovation in Improving Tuberculosis Transmission Prevention Behavior among Pulmonary TB Patients at Arifin Achmad Regional Hospital, Riau Province - Paridah; Defi Eka Kartika; Lita; Rani Lisa Indra; Abdur (CATHA SAINTIFICA, 2026)
Pulmonary tuberculosis (TB) spreads through patients’ daily behaviors such as coughing, mask use, and environmental hygiene all of which depend on how well patients understand TB and its prevenhannya. This study examined the relationship between knowledge and TB transmission prevention behavior among pulmonary TB patients at Arifin Achmad Regional Hospital, Riau Province. A quantitative analytic correlation design with a cross-sectional approach was used. A total of 85 respondents were selected through consecutive sampling according to inclusion criteria. Data were collected via questionnaire from January 13–27, 2026, at the Pulmonary Clinic, then analyzed univariately and bivariately. The majority of respondents were female (51.8%), mostly working as housewives (36.5%), and nearly seven out of ten had only completed primary school (69.4%). Almost all had no family history of TB (98.8%) and had never received prior TB education (97.6%). Bivariate analysis showed a significant relationship between knowledge and TB transmission prevention behavior. The numbers speak for themselves: patients with low education and no formal education tend not to know what to do. A routine and structured education program in the hospital is not merely complementary — it is part of prevention itself.